Konflik Berkepanjangan Ethiopia: Sebuah Penghampiran Mediasi Ethiopia-Tigray - Bimo Pragilaksono (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2022)
On November, 4th 2020, the Tigrayan Area became one of the deadly conflict hotspots in the midst of the global pandemic Covid-19. The conflicts are rooted since the Ethiopian People’s Democratic Front (EPRDF) becoming the governing party 30 years ago that reigned by corrupt, dirty, discriminate governance. EPRDF was in coalition with four parties: Amhara Democratic Party (ADP); The Oromo Democratic Party (ODP); Southern Ethiopian People’s Democratic Party Movement (SEPDPM); and Tigrayan People’s Liberation Front (TPLF). Among the four parties, only the TPLF has been promoted and acquired privileges by the EPRDF. These privileges provide TPLF an influence, an important political position, and a military sector, which creates other parties feel excluded. Political friction, sexual violence, and even the issue of ethnic cleansing of Tigrayans underlie the crisis. Since Abiy Ahmed from ODP become a new PM of Ethiopia, it is strongly indicated that his position indirectly supports reprisal against TPLF. The involvement of Eritrea in this conflict, expanding the spectrum of crisis. Deadlock on the solution and the unilateral claims of the Abiy’s successful (offensive) settlement against TPLF, agonizing the situation of the Tigrayan people. Therefore, in this essay, the author will explain how the characteristics of the current conflict situation, the ripeness of conflict, methods of resolution of mediation, and possible solution to construct a stable situation in the Tigray Conflict. Key Words: Abiy, Afrika, Amhara, Eritrea, Ethiopia, Oromo, Tigray, TPLF